Effect of azolla (Azolla pinnata) supplementation on puberty, semen characteristics and sexual behaviour in Alpine × Beetal crossbred bucks - KUMAR GUPTA, SHAILESH; CHANDRA, RAMESH; PRAKASH SHINDE, KULADIP; BHAKAT, MUKESH; AHMAD LONE, SHABIR; KUMAR, NISHANT (The Indian Journal of Animal Sciences, 2022)
The present experiment was conducted at ICAR-National Dairy Research Institute, Karnal, Haryana. Eighteenmale crossbred bucks (Alpine × Beetal) (average 103.94±2.87 days old) were divided into three groups withsix animals in each group, viz. T1 , T2 and T3 . Animals of T1 group were fed different green fodder and concentratemixture to meet their daily nutrient requirement. Animals of T2 group were fed according to T1 except 20% replacement of concentrate mixture by sun-dried azolla on DMB. Animals of T3 group were fed according to T1except the animals were fed with concentrate supplemented with 20% sun-dried azolla on DMB. Effect of azolla onage at puberty, seminal parameters and sexual behaviour was assayed by standard methods. The animals of T3group attained puberty significantly earlier as compared to T1 and T2 . Non-significant effect of azolla  upplementation on semen volume, pH, mass activity, abnormality and acrosomal integrity was observed. The progressive motility and sperm concentration was significantly higher in T3 group as compared to T1 . The HOST% and live spermatozoa were significantly higher in T2 and T3 as compared to T1 . Sexual behaviours were significantly better in T2 and T3 as compared to T1 . In conclusion, the supplementation of bucks with azolla reduces their age at puberty, improves seminal characteristics and sexual behaviour